SORPTION AND PERVAPORATION RESULTS OF CLINOPTILOLITE FILLED POLY(VINYLALCOHOL) MEMBRANE PREPARED FOR DEHYDRATION OF AQUEOUS ORGANIC MIXTURES - Salt, Yavuz; Arcevik, Ersel; Ekinci, Buket (WILEY-BLACKWELL, 2014)
Clinoptilolite filled poly(vinylalcohol) membranes containing different weight percentages of zeolite were prepared by solution casting method, and the prepared membranes were characterised by scanning electron microscopy, thermogravimetric analysis and differential scanning calorimeter. Sorption and permeation experiments were carried out at 30, 40 and 50 degrees C in pure water, ethanol (EtOH) and ethylacetate. In addition, the pervaporation separation of EtOH-water mixtures was conducted for 20-80wt% water containing EtOH-water binary mixtures at 30, 40 and 50 degrees C. It is observed that permeation rates increased and selectivity decreased with the increasing of temperature and the water content in the feed.
Keywords: mixed matrix membrane; sorption; permeation; zeolites; pervaporation; WATER-ISOPROPANOL MIXTURES; MIXED MATRIX MEMBRANES; COMPOSITE MEMBRANES; SODIUM ALGINATE; NANOCOMPOSITE MEMBRANES; SEPARATION; ZEOLITE; ADSORPTION; ALCOHOL); ETHANOL; Engineering